2013
DOI: 10.1371/journal.pone.0062291
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Analysis of Anthocyanin and Non-Anthocyanin Flavonoid in Various Tissues of Different Lotus (Nelumbo) Cultivars by HPLC-DAD-ESI-MSn

Abstract: A validated HPLC-DAD-ESI-MSn method for the analysis of non-anthocyanin flavonoids was applied to nine different tissues of twelve lotus genotypes of Nelumbo nucifera and N. lutea, together with an optimized anthocyanin extraction and separation protocol for lotus petals. A total of five anthocyanins and twenty non-anthocyanin flavonoids was identified and quantified. Flavonoid contents and compositions varied with cultivar and tissue and were used as a basis to divide tissues into three groups characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…Chen et al . () analysed the flavonoid composition and content in leaf pulps, leaf veins and leaf stalks of twelve cultivars lotus and found that the leaf pulps had the highest total flavonoid concentration. Lin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al . () analysed the flavonoid composition and content in leaf pulps, leaf veins and leaf stalks of twelve cultivars lotus and found that the leaf pulps had the highest total flavonoid concentration. Lin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Because the commonly used methods for extraction and separation, i.e., HPLC, UPLC, MS, or other analytical instruments, are more efficient and consume less organic solvents, they have been developed as efficient methods for plant-characteristic-constituents analysis [14-16]. Due to the complexity of the chemical compositions of different plant samples, the traditional integration methods [17] have been unable to simultaneously take into account the difference between content and activity.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the remarkable medicinal functions, plants of the genus Gentiana have been a hot topic in phytochemistry and pharmacology since the 1960s and exhibited chemical diversity (Wang et al ., ; Yang et al ., ). Additionally, more research demonstrated this genus is a rich source of iridoids and phenols such as gentiopicroside, swertiamarin, loganic acid, sweroside and mangiferin, which are commonly regarded as major constituents and likely to responsible for the different therapeutic effect of these folk medicines (Chen et al ., Ikeshiro and Tomita, ; Kakuda et al ., ; Ma et al ., ; Xu et al ., , , , ; Yang et al ., ; Zhang et al ., ). Therefore, the multicomponent analysis could be developed as an important approach for the quality evaluation of ethnomedicines from genus Gentiana .…”
Section: Introductionmentioning
confidence: 98%